PENDIDIKAN KARAKTER SEBAGAI PENGUATAN KONSEP DIRIDI PONDOK PESANTREN NURUL HUDA SURABAYA - Fitriasari, Andikawati; Buduri, Syiddatul; Khamida, Khamida (JURNAL NERS LENTERA, 2019)
Introduction : Adolescence is a vulnerable period in psychological development. Teenagers experience emotional turmoil that affects the process of forming self-concept. Islamic boarding school is believed to be an institution that can instill character values in adolescents. The purpose of this study is to determine the results of character education as a reinforcement of self-concept in the environment of the boarding school Nurul Huda Surabaya. Method: This research is a descriptive qualitative by cases in this study were teachers and students at Nurul Huda Islamic Boarding School Surabaya, which is the data collected through in-depth interviews and investigation. Results and Disscusion: The results of analysis based on character education and self-concept of the embedded character values are categorized into five-character values, their relationship with God, self, others, the environment, and nationality. Conclusion : Character education can strengthen adolescent self-concept, especially on self-identity, self-ideal and role in Nurul Huda Islamic boarding school. Character education will reinforce the self-concept of adolescents in the Nurul Huda boarding school environment. Keywords: Character Education, Self-Concept, Islamic Boarding School